Reexamining the Role of Vision in Second Language Motivation: A Preregistered Conceptual Replication of You, Dörnyei, and Csizér (2016). Issue 1 (1st August 2019) - Hiver, Phil; Al‐Hoorie, Ali H.
Abstract : Researchers have linked vivid mental imagery, particularly of the self in future states, to many desirable motivational outcomes for language learning. We report a preregistered conceptual replication and extension of You, Dörnyei, and Csizér (2016), who found a central motivational role for vision. We review essential considerations in structural equation modeling and discuss how the initial study addressed these, then describe a conceptual replication with a South Korean sample of secondary school learners of English ( N = 1, 297). Our analysis of the scales from the initial study in addition to second language achievement found support for an alternative model where the Intended Effort scale showed a better fit as a predictor of motivation than as an outcome variable. Our findings suggest the need for greater precision and rigor in structural equation modeling research on second language learning motivation and for more language researchers to take up replication and other open science initiatives. Open Practices: This article has been awarded Open Data, Open Materials, and Preregistered Research Design badges. All data and materials, along with preregistration for research design and analyses, are publicly accessible through the Open Science Framework at https://osf.io/v8gj4 . The study materials are also publicly available via the IRIS database at https://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science: https://osf.io/tvyxz/wiki . Abstract :